Post-Capital : A Reader - Cotton, Michelle (Luxembourg : Mudam Luxembourg - Musée d'Art Moderne Grand-Duc Jean, 2021)
Arakawa, Ei ; Fei, Cao ; Denny, Simon ; Laser, Liz Magic ; Pattison, Yuri ; Rowland, Cameron ; Syms, Martine ; Bourouissa, Mohamed ; Xiao, Guan ; Hiorns, Roger ; Novitskova ; Owens, Laura ; Pryde, Josephine ; Turato, Nora ; Favaretto, Lara ; GCC ; Habib Allah, Shadi ; Laric, Oliver ; Perry, Sondra ; Relph, Nick ; Steyerl, Hito
Post-Capital: A Reader is published as both a reader and a catalogue accompanying the exhibition Post-Capital: Art and the Economics of the Digital Age, curated by Michelle Cotton at Mudam Luxembourg. This richly illustrated volume documents works of sculpture, painting, photography, video, and performance by more than twenty artists from different parts of the world, all addressing production, consumption, and wealth. The images cohabit with excerpts from longer texts by some of today’s most influential thinkers on the subject of our digital age, its consequences concerning human freedoms, and the largely invisible dynamics that are driving an evolving and unequal world order. (provided by publisher)
Post-Capital. Art & the Economics of the Digital Age, Mudam Luxembourg- Musée d'Art Moderne Grand-Duc Jean, 02.10.20210-016.01.2022 ; Kunsthal Charlottenburg, Copenhagen, 17.09.2022-15.01.2023
boek